2019
DOI: 10.1002/lary.28150
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension Presenting as Auditory Neuropathy Hearing Disorder in a Child

Abstract: Otologic manifestations are known to occur in patients with idiopathic intracranial hypertension (IIH), but the occurrence of sensorineural hearing loss, especially in pediatric populations, has been addressed in only a few reports. Here, we describe a pediatric patient who presented with IIH and severe bilateral hearing loss. The patient's hearing loss was diagnosed as a form of auditory neuropathy (AN) and resolved after prompt treatment of the increased intracranial pressure. This case points to a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
0
6
0
6
Order By: Relevance
“…Os reflexos estapédicos estão ausentes ou presentes, porém com má morfologia a níveis muito elevados de intensidade, sugerindo uma disfunção a nível neuronal (Rance & Starr, 2015;Lang-Roth et al, 2017;Emami & Abdoli, 2019;Brough, 2020). Alguns autores especificam que devem ser as de 500Hz, 1KHz, 2KHz e 4KHz (Tobia et al, 2019;Fang et al, 2020).…”
Section: Diagnóstico Etiológico E Da Penaunclassified
See 2 more Smart Citations
“…Os reflexos estapédicos estão ausentes ou presentes, porém com má morfologia a níveis muito elevados de intensidade, sugerindo uma disfunção a nível neuronal (Rance & Starr, 2015;Lang-Roth et al, 2017;Emami & Abdoli, 2019;Brough, 2020). Alguns autores especificam que devem ser as de 500Hz, 1KHz, 2KHz e 4KHz (Tobia et al, 2019;Fang et al, 2020).…”
Section: Diagnóstico Etiológico E Da Penaunclassified
“…Nos estudos analisados a configuração da hipoacusia foi ascendente ou em "U" (Paquay et al, 2018;Wang et al, 2019). Além disto, os resultados da audiometria vocal não se encontram concordantes com o limiar auditivo, sendo estes piores que o esperado (Sagers et al, 2017;Dedhia et al, 2018;Wu et al, 2020), nomeadamente os valores da percentagem de discriminação com monossílabos entre os 0% e 16% (Tobia et al, 2019;Wang et al, 2019).…”
Section: Diagnóstico Etiológico E Da Penaunclassified
See 1 more Smart Citation
“…Since the intracranial pressure is evenly elevated in IIH, there is no neuroanatomic basis for preferential compression of the optic nerve [5]. In recent years, there have been reports of other cranial nerve [6] and auditory deficits [7] in addition to cognitive [8] and psychiatric disorders [9] in patients with IIH. This has led to a growing tendency to redefine IIH as a global neurologic syndrome [10].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study by C ¸oban et al (4) found that patients with IIH had significantly worse hearing levels compared with healthy individuals. While the exact incidence of hearing loss in patients with IIH is not known, hearing loss with or without tinnitus may be the only clinical manifestation of IIH in some patients (3,(6)(7)(8). Furthermore, some studies demonstrate that patients' audiovestibular complaints were reversed after treatment of their IIH, supporting the evidence that IIH was the cause of their symptoms (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%